THE IMPACT OF ARTERIAL HYPERTENSION ON LEFT VENTRICULAR STRAIN IN SEVERE AORTIC STENOSIS WITH PRESERVED EJECTION FRACTION. (June 2018) - Tadic, M.; Cuspidi, C.; Celic, V.; Ivanovic, B.; Pencic, B.; Bombelli, M.; Kocijancic, V.; Grassi, G.
Abstract : Objective: The influence of arterial hypertension on aortic stenosis (AS) severity is still controversial. However, the influence of arterial hypertension on left ventricular (LV) mechanics in AS patients has not been established yet. The aim of this study was to evaluate the influence of hypertension on LV strain in patients with severe AS. Design and method: This cross-sectional study included 78 subjects (45 men and 33 women) with severe AS and 65 normotensive age-matched controls (35 men and 30 women) who underwent comprehensive echocardiographic examination. Results: Hypertension was present in 43 AS patients. LV mass index was significantly higher in hypertensive AS patients comparing with normotensive AS participants (142 ± 26 vs. 119 ± 21 g/m2, p < 0.001). There was no significant difference in LV ejection fraction between hypertensive and normotensive AS patients. LV global longitudinal and circumferential strains were significantly lower in AS subjects than in controls. LV radial strain was not different between As and control subjects. Moreover, multidirectional LV strain was significantly lower in hypertensive than in normotensive AS participants (−14.3 ± 3.2 vs. −16.6 ± 3.0 %, p < 0.01 for longitudinal strain; and −17.5 ± 3.8 vs. −19.8 ± 3.4 %, p < 0.01 for circumferential strain). LV radial strain was not different between hypertensive and normotensive AS patients (41.3 ± 8.9 vs. 43.4 ± 9.1 %, p > 0.05). Evaluation of layer-specific LV strain showed that endocardial longitudinal and circumferential strains were significantly lower in hypertensive AS patients than in their normotensive counterparts. LV twist was significantly lower in AS patients than in controls (19.6 ± 5.3 degree vs. 23.2 ± 6.0 degree, p < 0.01). Hypertensive AS patients had significantly lower LV twist than normotensive AS subjects (17.2 ± 4.8 degree vs. 22.7 ± 5.8 degree, p < 0.01). Systolic blood pressure was associated with LV global longitudinal strain (β = 0.404, p < 0.01) and LV twist (β = 0.308, p < 0.01) in AS patients independently of LV mass index, age and BMI.β Conclusions: LV longitudinal and circumferential strains were significantly reduced in AS patients. Hypertension had additional significant negative influence on LV mechanics in patients with severe AS. Blood pressure was associated with LV global longitudinal strain and LV twist in AS patients independently of main clinical and demographic characteristics.